FACTORS CAUSING WIFE WORKS AND IMPACTS (CASE STUDY BRAJA SELEBAH DISTRICT OF EAST LAMPUNG DISTRICT) - Jaenuri, Jaenuri (LP3M STAI DARUSSALAM LAMPUNG, 2015)
Life in Indonesian society is still very often encountered some problemswithin a family, one of which is a matter of working wives. Islamicreligion does not forbid his wife to work even there are no rules on theprohibition of the wife works. In Sub Braja selebah wife works issue isstill very much encountered almost every wife to work. participationand wife work outside the home is still an issue discussed from the firstuntil now.This research is expected to provide insight for the developmentof science, especially in the areas of family law and can serve as areference for similar studies in the future. This research is a field thatis descriptive analysis. Data collection was conducted by interview,and documentation. And then analyzed using an inductive method ofthinking.The results showed that factors cause the wife works are internalfactors, namely: 1) factors and wife already worked before marriage2) factors that arise when the wife wants to change the economicsituation the family is still not very well be better 3) factors thatarise when there collision problems in the family needs. Externalfactors, namely: 1) factors that arise when their encouragement aswell as feedback from neighbors and relatives 2) Demands age 3)gender equality would be related to the emancipation of women 4)educational factors. Of course with the state of the working wife havea good impact on the positive or negative effects. The positive impactof the wife works, namely: 1) the economy for the better 2) Quality oflife improved 3) gender equality 4) establishment of family sakinahmawaddah wa Rahmah. Then the negative impact of the wife works,namely: 1) the divorce rate is increasing 2) juvenile delinquency 3)the loss of identity of the wife as mother 4) the number of pregnant mating phenomenon. Based on the results of research conducted inthe District of Braja Selebah East Lampung district, which is based ondata and interviews with respondents. That is a major factor in thewife works in the District Braja Selebah East Lampung district is amatter of economics.Keywords: Wife Work, Family, Braja Selebah